Liver Functional Status in Severe Forms of Covid-19 Disease (Eurasian Research Bulletin, 2023)
Changes occurring in the liver can be observed with direct exposure to the virus, systemic post-inflammatory cytokine attack (cytokine storm), hypoxia, hypovolemia in shock, hepatotoxicity of drugs. The body produces interleukins (IL-1b, IL-6, IL10) and chemokines that affect normally functioning hepatocytes. Viruses have been scientifically proven to affect the ACE2 and TMPRSS2 receptors in patients with Covid19, but in-depth studies show that if liver protectors are not taken during treatment and when the body's immune status is not controlled, liver cells are deeply affected as a result of this disease